The Role of the Police in Settlement of Land Confiscation Cases in Buol District - Mega Cahyani Y. Datu (Universitas Negeri Gorontalo, 2023)
This study aims to find out the role of the Police in solving land grabbing criminal cases, as well as what factors are the obstacles for the police in resolving land grabbing criminal cases. In this study, researchers used empirical research. This research was conducted at the Buol Polres, which was then conducted by looking at data on reports of cases of land grabbing in Buol district, as well as interviews with the Buol Resort Police. From the results of the study it can be seen that the police are very careful in resolving cases of criminal acts of land grabbing in Buol district. In the process of resolving cases of land grabbing by the Buol Resort Police, the reporter always prioritizes the importance of completing the data.